Breeding Practices of Goat Farmers Under Field Conditions in Perambalur and Ariyalr District of Tamilnadu - P. Suresh Kumar (The Indian Veterinary Journal, 2024)
A field survey was conducted to document the existing breeding management practices followed by goat farmers in Perambalur and Ariyalur district of Tamil Nadu. The study was conducted from the 240 farmers of 60 villages using pre-tested interview schedule. All the farmers followed the extensive system of rearing. The farmers were interviewed by using a pre- tested schedule and information was collected on the existing breeding practices through interaction with the farmers, personal observations. Breeding management practices included breeding methods, source of buck and doe for breeding, ratio of buck to doe, rotation of buck, period of rotation of buck, breeding season, kidding season. The study revealed that the main breeding season for goats was monsoon (24.17%) followed by summer (63.33%) and winter (12.50%). The main kidding season was winter (59.17%) followed by monsoon (38.33%) and summer (2.50%). The study suggested that non script goats of Perambalur and Ariyalur districts should be improved by educating the farmers to make them aware on advantages of selective breeding and also the superior bucks may be supplied to the goat farmers.